Anal polyp caused by Schistosoma mansoni - Pedro Raso; Eliane Mansur Sander; Leonardo Arruda Moraes Raso; José de Souza Andrade Filho (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
We describe a schistosomal polyp in the anus of a 24-year-old patient, born in Viçosa, State of Minas Gerais, and living in Belo Horizonte, State of Minas Gerais. From 8 to 13 years of age, he swam in the rivers that bathe Viçosa. The histopathological examination has shown a lesion, lined by a keratinized squamous epithelium, ulcerated, with granulomas, centered or not by Schistosoma mansoni egg, laid, in loco, by the female present in the vascular lumen of a vein of the hemorrhoidal plexus. There was also a diffuse, nonspecific inflammation in the dermis. The patient was treated with praziquantel. Four months after the treatment, sigmoidoscopy showed a normal rectal mucosa, and negative oogram and stool tests. Ultrasound of abdomen was normal.